2013
DOI: 10.5897/ajar12.2026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biomass production and nutritive value of nine Panicum maximum ecotypes in Central region of Benin

Abstract: The grassland resource could be better managed if the effect of different defoliation regimes on the amount of the dry matter and nutritive value was known. Consequently, 9 ecotypes of Panicum maximum were evaluated in central region of Benin with an average 1100 mm annual rainfall during 3 years for ley pasture without any fertiliser input. Three cutting regimes (3-10-3, 5-6-5 and 6-4-6-week) were tested for dry matter production (DM), crude protein (CP) content, CP production and mineral (Ca, Mg, P, K, Na, Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 11 publications
2
10
0
7
Order By: Relevance
“…Consequently, energy content (15.14 MJ/kg DM) was very high, though ash level was quite high too (16.42%DM). Macro-mineral: Ca, P, Mg and K contents are 5.87, 0.86, 1.69 and 11.04 mg/kg DM (Adjolohoun et al, 2013a;Musco et al, 2016).…”
Section: Issn: 2320-5407mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, energy content (15.14 MJ/kg DM) was very high, though ash level was quite high too (16.42%DM). Macro-mineral: Ca, P, Mg and K contents are 5.87, 0.86, 1.69 and 11.04 mg/kg DM (Adjolohoun et al, 2013a;Musco et al, 2016).…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…However, some ecotypes tolerate rainfall below 800 mm of water per year (Cook et al, 2005, Adjolohoun et al, 2008. Panicum maximum local can yield between 5-10 t/ha DM (Buldgen et al, 2001;Adjolohoun et al, 2013a). It has showed a very high CP (8-26% DM) and the low structural carbohydrates (NDF: 50.80%) content.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…Par ailleurs, d'un côté, il convient de souligner qu'en matière de graminées fourragères utilisées dans les UE, l'espèce P. maximum (92,48%) est de loin la graminée la plus produite devant l'espèce Penniseutum purpureum (30,79%) et le Sorghum bicolore ((30,35%), L'importance du choix de la graminée P. maximum serait liée à certaines de ses caractéristiques reconnues par les enquêtés. Il s'agit essentiellement de sa productivité en biomasse, sa résistance aux aléas climatiques notamment au stress hydrique, son appétence par les herbivores domestiques, sa résistance au feu de brousse, au broutage et au piétinement (Adjolohoun et al, 2012(Adjolohoun et al, , 2013. Ce qui rejoint les motivations des essais menés par l'ORSTOM dans les années 1960 sur l'espèce P. maximum ayant abouti à la sélection des cultivars très productifs et de bonne valeur fourragère (Toutain et al, 2009).…”
Section: Méthodes D'exploitation Des Espèces Fourragèresunclassified
“…Several studies have been conducted to test the effect of age of cutting on both yield and quality factors. Babatoundé (2005), Onyeonagu (2012), Adjolohoun et al (2013) and Gbenou et al (2018) commented that cutting frequency was the major factor that influenced the DM production and nitrogen concentration of grasses. Generally, studies conducted on the effect of cutting frequency on plant DM production showed that the more infrequent cutting, the higher the DM yields but the crude protein concentration and the proportion of digestible forage dropped correspondingly.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…In West Africa, pasture species evaluation with the objective of identifying the most productive and adapted species has been of interest for some years (Michiels et al, 2000 ;Buldgen et al, 2001;Babatoundé, 2005 ;Adjolohoun et al, 2013). Most of these species concerned exotic plants such as Pennisetum purpureum, Brachiaria.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%